Determination of the Shortest Path Using the Ant Colony Optimization (ACO) Algorithm Approach - Hengki Tamando Sihotang (ComTech: Computer, Mathematics and Engineering Applications, 2021)
Distribution is one of the essential activities in business because it determines the price of products or goods in the market. So, choosing the shortest path is considered one of the most important things in business, especially distributors. PT Everbright, one of the business actors engaged in the manufacture of batteries and as the main distributor, hopes that the distribution of goods to have the shortest route so that costs can be minimized. The aim of the research was to determine the shortest path in distributing goods in the Medan area to the location of consumers. The research used Ant Colony Optimization (ACO). Determination of the shortest path is based on distance calculations in kilometers, protocol roads, gangs, normal road conditions, and differences between small and major roads. Based on the research results, it is found that the J1 line has the greatest value. So, the path chosen by the ants to pass is J1 which is 11 km away from the departure location (PT Everbright) to the destination (Pasar Glugur Kota). It passes through PT Everbright --> Jln. Gatot Subroto --> Jln. Kapt. Muslim --> Jln. Tgk. Amir Hamzah --> Jln. KH. Syeikh Abdul Wahab Rokan --> Pasar Glugur Kota.